Desensitization Strategies for Donor-Specific Antibodies in HLA-Mismatched Stem Cell Transplantation Recipients: What We Know and What We Do Not Know - Yang Zhou; Yu-Lun Chen; Xi-Yi Huang; Ying-Jun Chang (Oncology and Therapy, 2024)
Abstract In human leukocyte antigen (HLA)-mismatched allogeneic stem cell transplantation settings, donor-specific anti-HLA antibodies (DSAs) can independently lead to graft failure, including both primary graft rejection and primary poor graft function. Although several strategies, such as plasma exchange, intravenous immunoglobulin, rituximab, and bortezomib, have been used for DSA desensitization, the effectiveness of desensitization and transplantation outcomes in some patients remain unsatisfactory. In this review, we summarized recent research on the prevalence of anti-HLA antibodies and the underlying mechanism of DSAs in the pathogenesis of graft failure. We mainly focused on desensitization strategies for DSAs, especially novel methods that are being investigated in the preclinical stage and those with promising outcomes after preliminary clinical application.